EVALUASI STASIUN KERJA CETAK DI HOME INDUSTRY MENGGUNAKAN METODE REBA DAN LINGKUNGAN KERJA FISIK (Inaque : Journal of Industrial and Quality Engineering, 2023)
XYZ cake mould home industry is a restaurant industry located in the city of Mojokerto, East Java. It is known that there are several abnormal worker positions in the Home Industry, namely at the printing workstation. Where Musculoskeletal Disorders (MSDs) occur, complaints or pain in certain parts of the body. These factors are affected by seating, hot workplaces, noise, and poor lighting. As a result, work productivity is erratic and tends to decrease. In this study, the Rapid Entire Body Assessment (REBA) method was used as the final step to determine the score for each operator activity and determine the severity experienced by the operator. And the highest score was obtained, namely 9 (nine) or the high-level category in the activity of making sand moulds and pouring molten aluminium. The environment also affects productivity, so the researchers used the Indoor Health and Comfort (IHC) method to determine the environmental conditions at the printing station. And get data starting from lighting 60 Lux, temperature 44o C, and noise 87.8 dB. From the physical environmental factors at the printing place, it is known that the value is not average. Keywords: Musculoskeletal Disorders (MSDs), Rapid Entire Body Assessment (REBA), Indoor Health and Comfort (IHC)